Antibiotic-Resistant Gram-Negative Bacterial Infections in Patients With Cancer - Perez, Federico (Clin Infect Dis, 2014)
Patients with cancer are at high risk for infections caused by antibiotic resistant gram-negative bacteria. In this review, we summarize trends among the major pathogens and clinical syndromes associated with antibiotic resistant gram-negative bacterial infection in patients with malignancy, with special attention to carbapenem and expanded-spectrum β-lactam resistance in Escherichia coli, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Stenotrophomonas maltophilia—all major threats to our cancer patients. Optimal therapy for these antibiotic-resistant pathogens still remains to be determined.